1996
DOI: 10.7883/yoken1952.49.151
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Impairments in Recurrent Plasmodium Vivax Infected Patients

Abstract: SUMMARY:The hematological parameters were assayed in Plasmodium vivax patients with only one infection, two infections, three infections and more than three malarial infections during a period of six months. A steady fall in the levels of hemoglobin as well as packed cell volume (PCV) level was observed with increasing number of infections. The malarial patients showed a progressive decrease in RBC level with increasing number of attacks. The decrease in the hematological indices was statistically significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Numerous reports have shown that P. vivax can be associated with severe anaemia [2-12]. Haematologic profiles of pancytopaenia in blood and bone marrow [16] and dyserythropoiesis in bone marrow [15] have been reported in vivax malaria patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reports have shown that P. vivax can be associated with severe anaemia [2-12]. Haematologic profiles of pancytopaenia in blood and bone marrow [16] and dyserythropoiesis in bone marrow [15] have been reported in vivax malaria patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most published reports on malaria-associated anaemia focus on Plasmodium falciparum with Plasmodium vivax being less well studied [1]. However, growing evidence from several geographic regions has demonstrated that P. vivax malaria is associated with a higher frequency and more severe anaemia [2-12]. Several cases of patients infected with P. vivax that resulted in severe disease and death were found to have syndromes resembling those commonly observed with falciparum malaria [8,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it appears that P. falciparum and P. vivax have evolved two different means of escaping splenic filtration. In both vivax and falciparum malaria, parasitized, and possibly non-parasitized, red cells are hypothesized to be more fragile than red cells in non-infected individuals and more prone to damage from shear stresses [72,81,110,112]. This process is potentially a more important cause of red cell loss in falciparum malaria since in this disease, major sequestration in the microvasculature impedes the passage of circulating erythrocytes and erythrocyte rosettes [82].…”
Section: Introductionmentioning
confidence: 99%
“…If this occurs before an individual’s haemoglobin concentration has returned to normal following primary infection, the haematological effects are likely to be additive though direct evidence supporting this postulate is limited [33,72,150]. The likelihood of repeat heterologous infection, and the probability that it occurs before complete haematological recovery, is a function of, among other things, the relapse pattern of local P. vivax strains and the entomological inoculation rate, both of which are also likely to affect the rate of genetic recombination and hence parasite population diversity [151].…”
Section: Introductionmentioning
confidence: 99%
“…[7] However, recent evidence shows that P. vivax-induced anemia is more frequent and more severe. [8][9][10] According to various theories factors contributing to anemia in vivax malaria are same as those mentioned in Table 1 but the role of immune-mediated hemolysis has been better attributed to anemia in falciparum malaria. [11] In autoimmune hemolytic anemia, antibodies are directed against antigens on the surface of RBC.…”
Section: Case Reportmentioning
confidence: 99%